Orang Kulisusu, Identitas dan Kekuasaan Reproduksi Identitas Kultural dalam Proses Pemekaran Kabupaten Buton Utara - Nurlin Nurlin (Antropologi Indonesia, 2014)
This article describes the relationship between power, history and identity in the processof division North Buton of Muna. In this article the presence of North Buton identity is seen asa phenomenon that refers to the identity of reproduction historical narrative where Kulisusuin historical context has a power relationship with the kingdom of Buton which lasted fromthe 17th century. This study found; that the presence of North Buton identity is a product ofdiscourse that legitimized by indigenous groups who identify themselves as descendants ofthe founder of the kingdom Kulisusu. it means that the identity of North Buton formed dueto higher power structures Barata Kulisusu surviving in culture Kulisusu People. This studyalso found that reproductive identity North Buton a political attempt to discover the identityof distinguishing between Kulisusu and People Muna (identity as a weapon of resistance).This distinctive identity in turn managed to attract popular support for the masses who feelconnected to that identity.Keywords: power; history; identity reproduction; regional division